#TITLE_ALTERNATIVE# - NURUL KAMILAH( NIM : 20111304)PEMBIMBING : Dr Kuntjoro Adji Sidarto, WULAN
Many empirical studies show the negative correlation between stock price changes and volatility changes. The Constant Elasticity of Variance (CEV), originally devel- oped by Cox,incorporates this negative correlation. There was a closed form solution derived by Cox, for pricing standard European option under CEV process, and for pricing European lookback option, we will use binomial approximation developed by Nelson and Ramaswamy (1990), and pricing algorithms developed by Costabile (2006). The results show the difierences between pricing option under CEV process and lognormal assumption, and of course it is much more important to have the correct model specification for estimate the option prices.